2015
DOI: 10.1093/mnras/stv1960
|View full text |Cite
|
Sign up to set email alerts
|

Model-free analysis of quadruply imaged gravitationally lensed systems and substructured galaxies

Abstract: Multiple image gravitational lens systems, and especially quads are invaluable in determining the amount and distribution of mass in galaxies. This is usually done by mass modeling using parametric or free-form methods. An alternative way of extracting information about lens mass distribution is to use lensing degeneracies and invariants. Where applicable, they allow one to make conclusions about whole classes of lenses without model fitting. Here, we use approximate, but observationally useful invariants form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Rather than thinking of external shear as a physical observable quantity, perhaps it makes most sense to instead think of it as a simple first order fitting parameter that represents information from several unknown effects. Whatever the case, Woldesenbet & Williams (2015) document the effects of external shear on the distribution of quads relative to the FSQ. Since this shear can provide deviations from the FSQ, we can experiment with nonzero values of shear and see if this is able to better match observations.…”
Section: Nonzero External Shearmentioning
confidence: 99%
“…Rather than thinking of external shear as a physical observable quantity, perhaps it makes most sense to instead think of it as a simple first order fitting parameter that represents information from several unknown effects. Whatever the case, Woldesenbet & Williams (2015) document the effects of external shear on the distribution of quads relative to the FSQ. Since this shear can provide deviations from the FSQ, we can experiment with nonzero values of shear and see if this is able to better match observations.…”
Section: Nonzero External Shearmentioning
confidence: 99%
“…Motivated to make a comparison to observables, we return to our model-free statistical measures of a population of quads: the radial position of images relative to the outermost image and the deviation from the FSQ resulting from the angular distribution of images. Woldesenbet & Williams (2015) showed that deviations from the FSQ for a single system can be caused by external shear or by deviations to the elliptical shape (Gomer & Williams 2018), while we have shown that shear can also reproduce the distribution or radial ratios. If shear were responsible for both quantities, then the innermost radial ratio and the deviation from the FSQ should be correlated.…”
Section: Role Of Shearmentioning
confidence: 61%
“…Meanwhile, the distribution of observed quads has significant spread from the FSQ. External shear causes the distribution to split above and below the FSQ, but is insufficient to account for the observed distribution (Woldesenbet & Williams 2015). However, the perturbations to the potential we use in our various tests can reproduce the observed distribution (Gomer & Williams 2018).…”
Section: Comparison With Observed Quadsmentioning
confidence: 87%
See 2 more Smart Citations